New genera for species of Jassa Leach (Crustacea: Amphipoda) and their relationship to a revised Ischyrocerini - Conlan, Kathleen E. (Zootaxa, 2021)
Four Southern Hemisphere and one Northern Hemisphere species of Jassa (Crustacea: Amphipoda: Ischyrocerini) are removed from this genus. The south temperate Jassa barnardi Stephensen, 1949 is synonymized with Ventojassa frequens (Chilton, 1883). The south temperate and subantarctic Jassa multidentata Schellenberg, 1931 and Jassa wandeli Chevreux, 1906 are transferred to Pleojassa n. gen., with the addition of P. lowryi n. sp., P. moorei n. sp. and P. orientalis n. sp. Hemijassa Walker, 1907 is resurrected for the Antarctic Jassa goniamera Walker, 1903. The Northern Hemisphere Jassa ocia (Bate, 1862) is transferred to Plumulojassa n. gen. and shown to range throughout the temperate coasts of the northeastern Atlantic and its eastern seas. Placed in context of the other genera of the Ischyrocerini Stebbing, 1899, Jassa, Pleojassa, Hemijassa and Plumulojassa join Parajassa Stebbing, 1899 in having a unique uropod 3 morphology. Characteristics of the uropod 3 and other appendages are used to revise four other genera of the Ischyrocerini. Ischyrocerus Krøyer, 1838 now becomes a temperate to polar genus, with Neoischyrocerus Conlan, 1995 embracing tropical species of Ischyrocerus and all members of Coxischyrocerus Just, 2009 and Tropischyrocerus Just, 2009. A new diagnosis and illustrated key to the 18 genera of Ischyrocerini is given.